2017
DOI: 10.5194/acp-17-9751-2017
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the mesospheric nighttime 4.3 µm emission puzzle: comparison of the CO<sub>2</sub>(<i>ν</i><sub>3</sub>) and OH(<i>ν</i>) emission models

Abstract: Abstract. In the 1970s, the mechanism of vibrational energy transfer from chemically produced OH(ν) in the nighttime mesosphere to the CO 2 (ν 3 ) vibration, OH(ν) ⇒ N 2 (ν) ⇒ CO 2 (ν 3 ), was proposed. In later studies it was shown that this "direct" mechanism for simulated nighttime 4.3 µm emissions of the mesosphere is not sufficient to explain space observations. In order to better simulate these observations, an additional enhancement is needed that would be equivalent to the production of 2.8-3 N 2 (1) m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 16 publications
4
28
0
Order By: Relevance
“…Remsberg et al (2008) found that the uncertainties associated with the CO 2 VMR contributed one of the largest sources of systematic error in the non-LTE region, with uncertainty values of 1. Feofilov et al, 2012;Panka et al, 2017), and the uncertainties associated with CO 2 (ν 2 ) vibrational quanta exchange rate constant (k vv ). García-Comas et al (2008) demonstrated that the non-LTE region T k (z) errors vary with both latitude and season and were largest during the polar summer (compared to a midlatitude summer location).…”
Section: 1029/2018jd028742mentioning
confidence: 99%
“…Remsberg et al (2008) found that the uncertainties associated with the CO 2 VMR contributed one of the largest sources of systematic error in the non-LTE region, with uncertainty values of 1. Feofilov et al, 2012;Panka et al, 2017), and the uncertainties associated with CO 2 (ν 2 ) vibrational quanta exchange rate constant (k vv ). García-Comas et al (2008) demonstrated that the non-LTE region T k (z) errors vary with both latitude and season and were largest during the polar summer (compared to a midlatitude summer location).…”
Section: 1029/2018jd028742mentioning
confidence: 99%
“…The model of Panka et al (2017) is the first one which accounts for the new vibrational relaxation pathway of OH(v) by collisions with O( 3 P) atoms…”
Section: Model and Retrieval Algorithmmentioning
confidence: 99%
“…This effect is, however, much more prominent in the OH VERs for channel 9 (middle panel). Unlike the higher vibrational levels, the lower ones are quenched by O 2 at a much slower rate (see Table 1 of Panka et al, 2017) and, therefore, reaction (2) plays here a more important role.…”
Section: Model and Retrieval Algorithmmentioning
confidence: 99%
“…In particular, Mlynczak et al (2018) changed the parameters of the SABER-2013 OH(v) model, which resulted in smaller nighttime O concentrations compared to SABER-2013, and hence a more realistic global annual mean energy budget of the MLT. Panka et al (2018) used the OH(v) model (Panka et al, 2017) for a novel algorithm which did not rely on the assumption of nighttime ozone equilibrium to derive nighttime O. This allowed the authors to eliminate the above-mentioned discrepancies between O distributions derived from SABER data and other satellite airglow observations.…”
Section: Introductionmentioning
confidence: 99%